Inclined Hole under Different Loading Conditions: A Review of Recent Results - Berto, F.; Afshar, Reza H. (Проблемы прочности, 2016)
Three-dimensional (3D) elastic stress distributions in the vicinity of the sharp corners of an inclined diamond hole in a plate are investigated. A detailed 3D finite element model under different loading conditions is analyzed to study the intensity of different fracture modes due to the thickness effect. The stress results are compared with those provided by a recent theory which reduces the 3D governing equations of elasticity to a differential equation system, which includes a biharmonic equation and a harmonic equation. They provide the solution of the corresponding in-plane and out-of-plane notch problem, respectively, and have to be concurrently satisfied. Comparing numerical results and theoretical stress distributions, a good agreement is found. Досліджено тривимірний пружний розподіл напружень біля гострих кутів похилого ромбоподібного отвору в пластині. Проаналізовано тривимірну скінченноелементну модель за різних умов навантаження для вивчення інтенсивності руйнування за різних мод з урахуванням товщини пластини. Отримані результати порівнюються з такими, що визначені за найновішою теорією, яка перетворює тривимірні основні рівняння пружності в систему диференціальних рівнянь, в яку входять бігармонічне і гармонічне рівняння. Останні забезпечують розв'язок, що відповідає умові в площині та поза площиною надрізу, і повинні одночасно задовольнятися. Отримано хорошу відповідність між чисельними результатами і теоретичним розподілом напружень. Исследовано трехмерное упругое распределение напряжений около острых углов наклонного ромбовидного отверстия в пластине. Проанализирована трехмерная конечноэлементная модель при различных условиях нагружения для изучения интенсивности разрушения при разных модах с учетом толщины пластины. Полученные результаты сравниваются с таковыми, определенными по новейшей теории, которая преобразует трехмерные основные уравнения упругости в систему дифференциальных уравнений, включающую бигармоническое и гармоническое уравнения. Последние обеспечивают решение, соответствующее условию в плоскости и вне плоскости надреза, и должны быть одновременно удовлетворены. Получено хорошее соответствие между численными результатами и теоретическим распределением напряжений.